Canções, diálogos e educação : caminhos para uma prática escolar humanizadora - Targas, Keila de Mello (2009)
The research question proposed by this study was: how can songs contribute to the appreciation of the cultural singularity in the school? What educative processes are generated from the contact of a teacher, her pupils and researchers? The objectives of the study were to observe, to describe and analyze the educative processes originated from the contact with the group, as well as to analyze how music contributed in this process. The research, of qualitative methodological ground, was developed in a public community school. With weekly meetings, the communication was done through music with songs, movements and body expression. The results show that music contributed to favor the dialogue between the different cultural and musical references in the group, in a perspective of appreciation and respect for the diversity and singularity.